Optical Properties of Germanium Nanoparticles Prepared by Laser Ablation - Riyadh, Shahad; Mohammed Salman Mohammad; Noorulhuda Riyadh Naser (University of Thi-Qar Journal of Science, 2023)
The synthesis of germanium nanoparticles (Ge NPs) through pulsed laser ablation in deionized water is investigated for Nanophotonics and optoelectronic applications. This study delves into the influence of laser pulse energy on Ge NP properties, specifically highlighting size control and optical characteristics. Our findings reveal a significant reduction in Ge NP size, from an initial 30 nm to 20 nm, as the laser pulse energy increases. Notably, we observed size-dependent blue luminescence from the synthesized Ge NPs. This controlled synthesis holds promise for optoelectronics and sensing applications. The study provides valuable insights into precise Ge NP synthesis and underscores their intriguing optical properties, paving the way for advanced Nanophotonic devices.